A really simple elementary proof of the uniform boundedness principle in F-spaces - Ansorena, José L. (Annales Mathematicae Silesianae, 2024)
We give a proof of the uniform boundedness principle for linear continuous maps from F-spaces into topological vector spaces which is elementary and also quite simple.